State Implementation of Welfare Law on Implementation of Human Rights in Local Governments - Agus Hamzah; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to determine the indicators of the realization of the welfare state law through development program documents. The approach method used is normative juridical. The conclusion of this research is that the welfare law state is often referred to as a modern law state in a material sense in the sense that the state or government is not merely the guardian of security or public order, but is the main bearer of the responsibility to realize social justice, public welfare, and as much prosperity people. As the social contract theory put forward by John Locke, and also Rousseau, which states, that the state obtains power from citizens as the holder of sovereignty solely to respect, protect and fulfill the human rights of citizens, implemented according to the Basic Law, the embodiment of the welfare state stated in the preamble to the 1945 Constitution, namely protecting the entire Indonesian nation and all Indonesian bloodshed and to promote public welfare, educate the nation's life and participate in implementing world order, This national goal contains the vision of the Indonesian people in the field of human rights and subsequently brought down in the vision and mission stated in the Regional Long-Term Development Plan (RPJPD) and the Regional Medium-Term Development Plan (RPJMD) which contain the vision and mission which can be an indicator of the realization of a welfare state law.